2021
DOI: 10.3390/su131910836
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Electricity Demand and Generation in Japan

Abstract: This research considered changes in monthly electricity generation and demand in Japan during the COVID-19 pandemic. Observed network electricity demand and generation type for the January–June 2020 period were compared to forecast values (using a triple exponential smoothing method) based on trends established from 2016 to 2019. Regional level electricity demand data showed little variation from expected trends for domestic energy users, but lower than expected business and industrial network demand, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Since the COVID-19 pandemic hit the world economy, many studies have revealed that energy-consumption patterns in various countries have been disrupted by the countermeasures, such as the lockdown, designed to prevent the spread of the coronavirus (Bahmanyar et al 2020;Aruga et al 2020;D'Alessandro et al 2021;Rouleau and Gosselin 2021). In many countries that implemented lockdown measures, it is suggested that although domestic electricity demand increased when people spent more time in their homes, the overall electricity consumption decreased as business and physical activities shrank severely; the reduction in commercial and industrial demand was greater than the increase in the domestic demand (Bahmanyar et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 pandemic hit the world economy, many studies have revealed that energy-consumption patterns in various countries have been disrupted by the countermeasures, such as the lockdown, designed to prevent the spread of the coronavirus (Bahmanyar et al 2020;Aruga et al 2020;D'Alessandro et al 2021;Rouleau and Gosselin 2021). In many countries that implemented lockdown measures, it is suggested that although domestic electricity demand increased when people spent more time in their homes, the overall electricity consumption decreased as business and physical activities shrank severely; the reduction in commercial and industrial demand was greater than the increase in the domestic demand (Bahmanyar et al 2020).…”
Section: Introductionmentioning
confidence: 99%